Magnetorresistência e correntes de spin em Multicamadas de Ni81Fe19/ZnO/Pd - Dugato, Danian Alexandre (2017)
In this work, we analyzed samples of thin films Ni81Fe19 and Pd with ZnO spacer. Ni81Fe19 is a ferromagnet with a low saturation magnetic field. Pd is a normal metal with high spinorbit coupling, much used in spin Hall effect and inverse spin Hall effect studies. ZnO is a semiconductor whose role is to reduce the charge current between layers. The sample have 5 nm of Ni81Fe19, 3 nm of Pd, and 2 nm of ZnO, with dimensions of 0.4 mm x 8 mm, deposited by magnetron sputtering. Using spin pumping we analyze the signal of the continuous voltage induced by ferromagnetic resonance. These samples the measured signal is a consequence of anisotropic magnetoresistance, anomalous Hall effect and inverse spin Hall effect. The thicknesses used contributes to a predominant inverse spin Hall effect signal. The ZnO spacer layer 2 nm reduces the effects of spin rectification, while maintaining spin current transfer.